Effect of Hepatitis E Virus on the Male Reproductive System: A Review of Current Evidence - Ahmed A. Kotb; Mohamed A. El-Mokhtar; Ibrahim M. Sayed (Viruses)
Hepatitis E Virus (HEV) is a globally widespread pathogen that causes acute hepatitis infection. Beyond hepatic pathogenesis, HEV has been proven to cause several extrahepatic manifestations, such as neurological, renal, and hematological manifestations. It was also associated with mortality in pregnant females. Several studies have investigated the impact of HEV on the male reproductive system; however, the available data are limited and conflicting. Assessment of the patients’ ejaculates/semen samples revealed that HEV particles are excreted in these fluids in cases of chronic infection but not acute infection. The excreted HEV particles are infectious to in vivo animal models and in vitro cell culture. However, the effect of HEV infection on male infertility is not confirmed. One study including human samples showed male infertility associated with HEV genotype 4 infection. Studies of HEV infection in animal models such as pigs, gerbils, and mice showed that HEV infection caused distortion on the testes, damage of the blood–testis barrier, and induction of inflammatory responses leading to abnormalities in the sperm. The excretion of HEV in the semen fluids raises concerns about HEV transmission via sexual transmission. However, all available data do not confirm the transmission of HEV through sexual intercourse. This review aims to summarize and critically assess the available studies investigating the influence of different HEV genotypes on the male reproductive system, providing insights into whether HEV contributes to reproductive impairment in men.